2016
DOI: 10.1097/md.0000000000003515
|View full text |Cite
|
Sign up to set email alerts
|

Lower Health-Related Quality of Life in Polytrauma Patients

Abstract: Although trauma-associated mortality has fallen in recent decades, and medical care has continued to improve in many fields, the quality of life after experiencing polytrauma has attracted little attention in the literature. This group of patients suffer from persisting physical disabilities. Moreover, they experience long-term social, emotional, and psychological effects that limit/lower considerably their quality of life.We analyzed retrospective data on 147 polytraumatized patients by administering written … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 26 publications
2
32
0
2
Order By: Relevance
“…Therefore, it is not surprising that patients after a thoracic or thoracolumbar fracture that required both posterior and anterior stabilization do not regain the same QOL as compared to a general population [29,30]. This is in correspondence with the existing literature on QOL in trauma patients, in which traumatically injured patients [31] and especially severely injured patients (ISS ≥ 16) [32,33] do not regain general population values. Furthermore, on some domains QOL is not fully decreased and comes back to population values.…”
Section: Quality Of Lifesupporting
confidence: 70%
“…Therefore, it is not surprising that patients after a thoracic or thoracolumbar fracture that required both posterior and anterior stabilization do not regain the same QOL as compared to a general population [29,30]. This is in correspondence with the existing literature on QOL in trauma patients, in which traumatically injured patients [31] and especially severely injured patients (ISS ≥ 16) [32,33] do not regain general population values. Furthermore, on some domains QOL is not fully decreased and comes back to population values.…”
Section: Quality Of Lifesupporting
confidence: 70%
“…It is well recognized that a greater intensity of the traumatic event reflects a greater repercussion on the HRQOL score; 4 the recent study of Zwingmann et al showed that polytraumatized patients had lower scores in each domain of SF-36, as compared to those of the age-and gendermatched population norm. 13 Therefore, HRQOL is an increasingly used tool in clinical practice. It serves to evaluate the results of treatment and also helps to select optimal therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
“…There is presently a lack of data regarding physical and psychological impairment in such injuries, 4,[9][10][11] but health-related quality of life (HRQOL) protocols after facial trauma have been well recognized and adopted. 4,[12][13][14] The main purpose of the current study was to compare the 36-Item Short Form Health Survey (SF-36) scores of surgically treated maxillary and zygomatic fractures in male patients with the reported normative data of SF-36 for the Croatian population. The secondary aim was to correlate important clinical variables with different concepts of the SF-36.…”
Section: Introductionmentioning
confidence: 99%
“…Turk and Okifuji differentiated acute and chronic pain using criteria for duration and pathology, short‐lasting pain with high physical pathology reflects acute pain, whereas prolonged durations with low pathology represent chronic pain . However, most chronic pain conditions in adults represent an interplay between significant nociceptive inputs and psychosocial/cognitive factors . The ‘expected healing period’ for defining transitions from acute to chronic pain is variably pegged at one, three or six months .…”
Section: Previous Studies On Persistent or Chronic Pain In Newbornsmentioning
confidence: 99%